Identification and Characterization of Bovine Viral Diarrhea Virus from Indonesian Cattle (IDENTIFIKASI DAN KARAKTERISASI VIRUS BOVINE VIRAL DIARRHEA DARI SAPI INDONESIA) - Saepulloh, Muharam; Sendow, Indrawati (Jurnal Veteriner; Vol 16 No 1 (2015), 2015)
Bovine viral diarrhea virus (BVDV) is an important viral disease, which a ubiquitous pathogen ofcattle with worldwide economic importance and due to its misdiagnose with other viruses. The goal of thecurrent study was to identify and characterize of BVDV by reverse transcriptase polymerase chainreaction (RT-PCR) and followed by sequence genome analyses. Blood, feces, and semen samples werecollected from 588 selected cattle from animals suffering from diarrhea and respiratory manifestation. RTPCRresults showed that the 69 (11.74%) samples were positive to BVDV. Further molecularcharacterization was conducted only with 17 PCR positive samples. The results indicated the 17 IndonesianBVD virus isolates were belonging to the genotype-1 of BVDV (BVDV-1) based on sequence analysis anda phylogenetic relationship between Indonesian BVDV isolates and BVDV in the world. This finding is thefirst report of BVD-1 circulated in Indonesian cattle.
Keywords: BVDV, RT-PCR, genotype-1